Dzielimy się doświadczeniemFalse aneurysm of left ventricle - Mak, Marek; Nasuszny, Wojciech; Jarek, Darek; Stanisławski, Ryszard; Klausa, Filip; Rogulski, Łukasz; Kustrzycka-Kratochwil, Dorota; Toczek, Krzysztof; Skiba, Jacek; Banasiak, Waldemar (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Acute post-myocardial infarction aneurysms of the left ventricle are a very rare, life-threatening complication of myocardial infarction. The authors present surgical treatment of three morphologically different types of heart pseudoaneurysms